2012
DOI: 10.1111/j.1445-5994.2011.02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis subtypes in symptomatic and asymptomatic family members and pets and response to therapy

Abstract: Conventional therapy is ineffective for symptomatic Blastocystis infection. The high prevalence of Blastocystis infection within households suggested transmission between humans and their pets. Subtyping analysis of SSU rDNA alone in Blastocystis does not appear to predict pathogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 49 publications
6
70
0
2
Order By: Relevance
“…Interestingly ST4, which is considered rare outside of Europe ) but has been detected in Australia (Nagel et al, 2014;Nagel et al, 2012), was not present in our dataset. However, this could be due to the low number of individuals that were positive for Blastocystis -further sampling of individuals from different regions is required to definitively establish the incidence and distribution of ST4 in the US.…”
Section: Etc)mentioning
confidence: 45%
“…Interestingly ST4, which is considered rare outside of Europe ) but has been detected in Australia (Nagel et al, 2014;Nagel et al, 2012), was not present in our dataset. However, this could be due to the low number of individuals that were positive for Blastocystis -further sampling of individuals from different regions is required to definitively establish the incidence and distribution of ST4 in the US.…”
Section: Etc)mentioning
confidence: 45%
“…In many studies, pathogenic potential of subtype 3 has been reported (16,31,(33)(34)(35). Also, some investigations have demonstrated that other subtypes such as subtype 1 were associated with symptoms (20,31,34,36).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the pathogenesis of B. hominis subtypes is not investigated but some differences in virulence between Blastocystis subtypes was shown (9,20,31,32). In many studies, pathogenic potential of subtype 3 has been reported (16,31,(33)(34)(35). Also, some investigations have demonstrated that other subtypes such as subtype 1 were associated with symptoms (20,31,34,36).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of ST9 only found in humans, the other 8 STs show low to moderate host specificity also by inhabiting various animal groups [3,23,24]. Many authors include these animal groups as representatives of potential reservoirs of zoonotic transmission [16,25]. One more confirmation for the zoonotic potential of Blastocystis sp., is the high occurrence of this parasite among people handling animals, compared with those without contact with animals [18,20,26].…”
Section: Objectivementioning
confidence: 99%
“…People are colonized mainly by ST1 through ST4, containing over 90% of assessments; but depending on the regions and countries, infection by ST5 through ST9 is also detected [10,20]. Nevertheless, that ST3 is the most common ST in humans worldwide, and its occurrence is a frequent finding in analyses of ST distribution, regardless of the geographic derivation of the population [18,25,49,50].…”
Section: Pathogenicity Of Blastocystis Sp Is a Relationship Possiblementioning
confidence: 99%